A ZigBee network anonymous authentication scheme based on Chebyshev chaotic mapping and CRT - Wei LIAO; Lesheng HE; Heng YIN; Shengtao YU; Jiarui QUAN (物联网学报)
A ZigBee network anonymous authentication scheme based on Chebyshev chaotic mapping and Chinese remainder theorem (CRT) was proposed to solve the problems such as the incomplete reliability of ZigBee network trust center and the lack of identity authentication when accessing the network.The proposed scheme can not only realize two-way authentication of anonymous identity, but also ensure the security of key distribution when ZigBee network structure changes dynamically.It is mainly based on a ZigBee and NB-IoT wireless heterogeneous gateway, so that the server can effectively manage the nodes in the network through this gateway.From security analysis and comparison with other related literature, the proposed scheme has higher security, with anonymity and unlink ability.In addition, the results show that the proposed scheme has more advantages than other schemes on the computational overhead.